Persepsi Remaja Putri di Kota Ambon Tentang Risiko Terpapar Kosmetik Berbahaya dan Perilakunya dalam Memilih dan Menggunakan Kosmetik - Bidan Tringani Damanik, Kristiana Etnawati, Retna Siwi Padmawati (Berita Kedokteran Masyarakat (BKM), 2011)
Perception of Female Teenagers In Ambon About Hazardous Cosmetics Exposure Risk and Their Behavior of Choosing and Using CosmeticsBackground: Cosmetics are products that frequently used by female teenagers to attain and maintain beauty instantly according to their beauty concept. There are many cosmetics in the markets unregistered and contain hazardous substances. The wide distribution of unregistered cosmetics becomes a risk factor for hazardous cosmetics exposure. Thus a research is needed to study  the perception of female teenager about hazardous cosmetics exposure risk and their behavior of choosing and using them.Objective: This research intended to study the  perception of female teenagers about hazardous cosmetics, the perception of female teenagers in Ambon about hazardous cosmetics exposure risk and the behavior of choosing and using cosmetics.Method: This research was a survey combined with qualitative method using descriptive explorative approach. Survey was conducted in in 6 private and 6 public High Schools in Ambon. There were 394 female students as responden which is recruited by multistage cluster sampling method. The methods of data collection were descriptive and Focus Group Description (FGD). The participant of FGD was recruited  with purposive sampling method, in which  3 to 4 students from each school recruited as participants of FGD yielding a total of 44 respondents who were split in 6 group discussion.  Thematic was then used for data analysis.Results: More than half of 394 students (57,9%) experienced skin problem after using their cosmetics. The evidence of some skin problems such as  peeled off the skin, reddish skin and burned skin was perceptioned as procedures to make skin become white, but the black spot and acne after using cosmetics was perceptioned as the cosmetics is dangerous.Conclusion: The wrong perception that some skin problems are the procedure to make skin white in teenagers in Ambon,  lead them  to have the risky behaviour in choosing and using cosmetics. The National Agency of Food and Drug Control especially the Institute of Food and Drug Control in Ambon should actively conduct  the health promotion about cosmetics and problems in the high schools and household in  to reduce the potential risk of the exposure to hazardous cosmetics.Keywords: beauty concept, perception, cosmetics, hazardous cosmetics, the behavior of choosing and using cosmetics